Chitooligosaccharide Maintained Cell Membrane Integrity by Regulating Reactive Oxygen Species Homeostasis at Wounds of Potato Tubers during Healing - Pengdong Xie; Yangyang Yang; Di Gong; Lirong Yu; Ye Han; Yuanyuan Zong; Yongcai Li; Dov Prusky; Yang Bi (Antioxidants, 2022)
Chitooligosaccharide (COS) is a degradation product of chitosan. Although COS increased fruit resistance by regulating the metabolism of reactive oxygen species (ROS), few reports are available on whether COS regulates ROS homeostasis at wounds of potato tubers during healing. In this study, COS increased gene expression and activities of NADPH oxidase and superoxide dismutase, and promoted the generation of O2●− and H2O2. Moreover, COS increased gene expression and activities of catalase, peroxidase, and AsA–GSH cycle-related enzymes, as well as the levels of ascorbic acid and glutathione levels. In addition, COS elevated the scavenging ability of DPPH, ABTS+, and FRAP, and reduced cell membrane permeability and malondialdehyde content. Taken together, COS could maintain cell membrane integrity by eliminating excessive H2O2 and improving the antioxidant capacity in vitro, which contributes to the maintainance of cell membrane integrity at wounds of potato tubers during healing.